PENGARUH PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL) TERHADAP HASIL BELAJAR MATEMATIKA - Hidayatin, Nuril (Buana Matematika : Jurnal Ilmiah Matematika dan Pendidikan Matematika, 2016)
Students often have difficulty in linking the material with the problems of life in the real world. This may result in a decrease in mathematics learning outcomes in schools. Therefore, teachers should be able to make learning fun during the learning process. To overcome these problems, teachers can use the approach Contextual Teaching and Learning (CTL) during learning process. This contextual approach to make students more active and to encourage students to make connections between knowledge and real-life situation. The purpose of this study was to determine whether there is influence approach Contextual Teaching and Learning (CTL) on learning outcomes mathematics SMP Negeri 4 Waru Academic Year 2015-2016. During the learning activities, the experimental class students formed into groups. Each group consisted of 4-5 students. During the learning process, the researchers fed the material set in the experimental class and the control class as samples in the study. Researchers chose the material set for the number of students who have difficulty in solving the problem set. To obtain the data result of learning mathematics, researchers took data from the pre-test and post-test. Pre-test given to students to find out how the students' abilities before receiving material taught by researchers, while the post-test was given to determine student learning outcomes after the student has finished the learning activities. Both of these classes have the same number of students is 32 students. In this study, found that with and. From these results it is rejected and Ha is it can be concluded that there is influence approach Contextual Teaching and Learning (CTL) on learning outcomes mathematics SMP Negeri 4 Waru Academic Year 2015-2016. Keywords: CTL (Contextual Teaching and Learning), sudent’s achievement.